EVALUASI SOFTSKILL MAHASISWA BERBASIS ANDROID DENGAN ALGORITMA DYNAMIC PROGRAMMING - Mahrus Ali (Universitas Muhammadiyah Semarang, 2017)
According to the results of search and study (Illah Sailah, 2008) there is a difference of needs and development as well as the point of view of hard skills and soft skills between the world of work and college at the current ratio of soft skills and hard skills needs in the world of work / business inversely proportional to its development in college. Success in the world of work / effort 80% is determined by the mindset (soft skills) it has and 20% determined by technical skills (hard skills). In Wikipedia (2010) it iswritten that soft skills is a sociological termination for an individual's Emotional Intelligence Quotient (EQ), an ability of how people relate to one another, such as communicating, listening, giving feedback, working together in a team , solve problems, contribute to meetings, and resolve conflicts. However, the condition of university students hasyim asy'ari is not aware of the importance of softskill ability. Therefore, researchers make an application to measure or self-assessing students related to sofskill based on android with dynamic programming algorithm. Because android applications are now mushrooming among young people, especially students. this application can display the score of the value amount of softskill.Keywords: Algorithm Dynamic programming, softskill, Android